In pursuit of a panacea: mitigating human-baboon conflict in the Cape Peninsula, South Africa - Kaplan, Bentley (Department of Biological Sciences, 2022)
With its unparalleled growth and distribution, the human species is increasingly conflicting with wildlife over crops, livestock and even human life as it infringes on natural habitat. In the Cape Peninsula, South Africa, urbanisation has simultaneously reduced the availability of productive low-lying natural land and provided plentiful high-caloric anthropogenic food items within urban, rural and tourist areas. The chacma baboons that occur in the Cape Peninsula have adapted to exploit this anthropogenic food, bringing them into direct conflict with humans. Despite the use of a costly management strategy (baboon monitors/herders), conflict between the two species persists in the form of property damage and stress to local residents and injury and mortality to baboons. The primary aim of this thesis was to explore new approaches for mitigating human-baboon conflict by experimentally manipulating various facets of the cost-benefit ratio to baboons entering human environments. Initially, I tested the efficacy of three deterrents, namely light prisms, bear bangers and electric fencing in raising the costs of entering human environments and therefore reducing baboon use of those environments. Light prisms were completely ineffective in achieving this end, while bear bangers and electric fencing showed prolonged success with no evidence of habituation. An alternative to raising the cost to baboons of entering human environments (deterrents) is to increase the relative benefits of remaining in natural areas, through provisioning food. Indeed, by manipulating the despotic leadership present in chacma baboons through a feeding patch, I was able to affect a shift in a troop's ranging pattern away from human environments. However, this shift was only significant where access to food in the human environment was restricted. Guided by this finding, I then tested the efficacy of baboon-proof waste bins in excluding baboon access and thereby reducing the benefit of human environments. While the bins were highly effective, their success was contingent on proper use and cooperation by residents. In this vein – to aid collaborative management of the baboon population – I conducted a survey of Cape Peninsula residents concerning various aspects of human-baboon conflict. Primarily, residents indicated a considerable tolerance for baboons despite the generally negative baboon-experience profiles. Further, residents had a poor understanding of baboon management structures as well as baboon conservation status, a finding that requires urgent attention where debates around baboon management are nuanced and emotive. I propose the use of two-way communication platforms (online social networks) that will help to minimise ever-present human-human conflicts. Ultimately, human-wildlife conflict is the combination of constraints imposed by cost, socio-ecological values and animal welfare and arguably it can only be ameliorated through multi-stakeholder engagements; the success of which is contingent on sound scientific data.